2003
DOI: 10.1046/j.1467-8624.2003.00632.x
|View full text |Cite
|
Sign up to set email alerts
|

Children and Adolescents' Internal Models of Food‐Sharing Behavior Include Complex Evaluations of Contextual Factors

Abstract: This study examined internal representations of food sharing in 589 children and adolescents (8 -19 years of age). Questionnaires, depicting a variety of contexts in which one person was asked to share a resource with another, were used to examine participants' expectations of food-sharing behavior. Factors that were varied included the value of the resource, the relation between the two depicted actors, the quality of this relation, and gender. Results indicate that internal models of food-sharing behavior sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
(53 reference statements)
1
14
0
Order By: Relevance
“…Empirical evidence indicates that trusted partners do not closely track particular exchanges and are not easily provoked into defection by a partner's occasional defection (Silk, 2003). Moreover, humans are more willing to engage in costly cooperation with trusted partners than with strangers, and thus are not generally NICE in the way that successful strategies often are in the IPD (Markovits et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidence indicates that trusted partners do not closely track particular exchanges and are not easily provoked into defection by a partner's occasional defection (Silk, 2003). Moreover, humans are more willing to engage in costly cooperation with trusted partners than with strangers, and thus are not generally NICE in the way that successful strategies often are in the IPD (Markovits et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This is probably related to the fact that money can be stored, be converted into other reward currencies and taken on large values (Rosati, Stevens, Hare, & Hauser, 2007). Sharing food, on the other hand, depends on who are the partners -relatives, friends, and strangers -and on the expectation of future positive interaction (Markovits et al, 2003). Moreover, food is perishable and more difficult to store.…”
mentioning
confidence: 99%
“…Stickers (Benenson, Pascoe, & Radmore, 2007;Blake & Rand, 2010;Gummerum, Hanoch, Keller, Parsons, & Hummel, 2010;Lucas, Wagner, & Chow, 2008), food (Brownell, Svetlova, & Nichols, 2009;Fehr & Fischbacher, 2003;House et al, 2012;Markovits, Benenson, & Kramer, 2003), and money (Gummerum, Keller, Takezawa, & Mata, 2008;Harbaugh, Krause, & Liday, 2003;Leman et al, 2009) have been used to investigate cooperative behavior in children, in a variety of experimental designs. However, to our knowledge only one study have recently compared the effect of different kind of resources on cooperation in 3-year-old children and have found no differences (Warneken, Lohse, Melis, & Tomasello, 2010).…”
mentioning
confidence: 99%
“…Silva (2013) suggests that children assess the value of the object in this selection process and donate less when they perceive the object as more valuable. Moreover, they consider not only the value of the resource itself but also mainly the value according to the context -split a biscuit in a park or a sandwich in a forest (Markovits et al, 2003). House, Henrich, Brosnan and Silk (2012) observed that older children laughed when sharing less items with the receiver, probably because it is contrary to one's expectations.…”
Section: Resultsmentioning
confidence: 99%
“…"Disinterested" help in front of an interested audience makes the individual gain in reputation, being socially rewarded and attracting cooperation (Nowak & Sigmund, 1998;Panchanathan & Boyd, 2003). Markovits, Benenson and Kramer (2003) conducted a study with elementary, junior and senior high school and undergraduate students and suggest that the pattern of sharing can be seen as a mutual influence of different factors. Participants were exposed to contexts that required sharing (a dessert biscuit in a park, low survival value, or a sandwich in a forest in which the actors are lost, tired, and hungry, high survival value) and distinct degrees of kinship or familiarity with the individual who was beneficiated (a relative -brother, a classmate or a stranger).…”
Section: Introductionmentioning
confidence: 99%